The Determinant Factors of Ethical Purchasing Intention : Does Religiosity Matter? - Krisjanti, Mahestu N.; Harsono (Indian Journal of Marketing, 2025)
Purpose : This study evaluated the impact of religion, moral obligation, and perceived customer effectiveness (PCE) on consumers’ ethical purchasing intentions. Design/Methodology/Approach : The data from 317 respondents were analyzed using Smart-PLS to determine the impact of determinant factors and the mediating roles of moral obligation and PCE. Findings : The findings indicated that religiosity influenced moral obligation, PCE, and ethical purchasing intention. PCE mediated the relationship between religiosity and the intention to make ethical purchasing decisions. Research Limitations/Implications : The study’s indicators of moral obligation might lead to differing perceptions among respondents; therefore, these indicators should be refined for future research. Practical Implications : The study helped the managerial side develop strategies to attract consumers to purchase the products ethically. Social Implications : The intention to purchase products ethically became a significant issue in the market due to the lack of ethical behavior among consumers. Therefore, this research’s findings have a social impact on improving consumer ethical purchasing intention by using religiosity as a determinant factor. Originality/Value : The research contributed to the evaluation of the role of religion in shaping ethical consumer purchasing intentions.